A Multiresponsive Calix[6]arene Pseudorotaxane Empowered by Fluorophoric Dansyl Groups. Issue 22 (16th March 2023) - Andreoni, Leonardo; Beneventi, Giovanni Mariano; Giovanardi, Gabriele; Cera, Gianpiero; Credi, Alberto; Arduini, Arturo; Secchi, Andrea; Silvi, Serena
Abstract: We report the synthesis and characterization, by means of NMR and UV‐visible spectroscopy and electrochemical techniques, of a dansyl calix[6]arene derivative and of its pseudorotaxane complex with a bipyridinium‐based axle. This novel macrocycle shows remarkable complexation ability, in analogy with parent compounds, while the dansyl moieties impart valuable features to the system. Indeed, these units: i) signal the state of the system by fluorescence; ii) can be reversibly protonated, enabling the modulation of the complexation abilities of the macrocycle; iii) participate in photoinduced electron transfer processes, which may be exploited to tune the stability of the supramolecular complex. Therefore, in this multiresponsive pseudorotaxane, the threading and de‐threading motions of the molecular components can be modulated either by protonation of the calixarene host or by reduction of the bipyridinium guest, which can be accomplished both by electrochemical reduction and via photoinduced electron transfer. Overall, three orthogonal and reversible stimuli can be used to induce molecular movements of the pseudorotaxane components. Abstract : A multiresponsive pseudorotaxane, composed by a dansyl calix[6]arene and a bipyridinium axle, is presented. The disassembly of this complex can be triggered by: i) protonation of the dansyl units (chemical stimulus); ii) electrochemical reduction of the bipyridinium unit (electrochemical stimulus); iii) photochemical reduction of the bipyridinium unit, enabled by photoinduced electron transfer from the dansyl units (light stimulus). Overall, three orthogonal and reversible stimuli can be employed to control the stability of this novel pseudorotaxane.